2020
DOI: 10.3390/economies8040080
|View full text |Cite
|
Sign up to set email alerts
|

Financial Inclusion and Firms Growth in Manufacturing Sector: A Threshold Regression Analysis in Selected Asean Countries

Abstract: This paper examines the effect of financial inclusion on the firm growth of the manufacturing sector (513 firms) in selected ASEAN countries (Malaysia, Philippines, and Vietnam) using a cross-section threshold estimation technique. The levels of financial inclusion across firms were measured based on the distribution of financial services (access to credit). The main findings revealed that there is a non-monotonic effect of financial inclusion on the firm’s growth. These findings show that the impact of financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…Ratnawati [80] found explicit confirmation regarding increased access to financial services, including access to credits, leading to the growth of market share, sales and the number of workers for micro, small and medium companies. Similar findings could be seen in other studies where Le et al [81], and Yang & Zhang [54] generalized that the FI determined a company's positive growth and performance. However, some scholars had inconsistent findings [81] to the present study, stating that FI does not influence SMEs.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Ratnawati [80] found explicit confirmation regarding increased access to financial services, including access to credits, leading to the growth of market share, sales and the number of workers for micro, small and medium companies. Similar findings could be seen in other studies where Le et al [81], and Yang & Zhang [54] generalized that the FI determined a company's positive growth and performance. However, some scholars had inconsistent findings [81] to the present study, stating that FI does not influence SMEs.…”
Section: Resultssupporting
confidence: 89%
“…Similar findings could be seen in other studies where Le et al [81], and Yang & Zhang [54] generalized that the FI determined a company's positive growth and performance. However, some scholars had inconsistent findings [81] to the present study, stating that FI does not influence SMEs. However, FI aims to offer financial services and products through safe, affordable and community-wide accessibility to alleviate poverty and inequality.…”
Section: Resultssupporting
confidence: 89%
“…The study conducted on the data from 2005 to 2016 found that achieving a threshold level of financial inclusion helps control corruption. In Malaysia, the Philippines, and Vietnam, the effect of access to formal credit on manufacturing firms' growth was studied by Nizam, Karim, Sarmidi, and Rahman (2020b). They found a non-monotonic impact of financial inclusion on the firm's growth, i.e., it is significantly positive below a threshold point, but beyond a certain point, it becomes negative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of threshold regressions stems from the need to model nonlinear relationships and fit a model that allows obtaining an estimate of the threshold and the coefficients of the explanatory variables on each side of the threshold. Various investigations support the usefulness of the methodology proposed by Hansen [14,[58][59][60][61][62][63][64][65]. The tests performed before estimating the final threshold model should be emphasized.…”
Section: The Modelmentioning
confidence: 99%